THE IMPACT OF THE COVID-19 PANDEMIC ON GREEN STOCKS PRICES: EVIDENCE FROM STOCKS WITHIN THE SRI-KEHATI INDEX IN INDONESIA - Ferdian Pradana, Christoforus
The recent years saw an increase in green investing, which is investing in green or environmental stocks. Green stocks are shares from a company that has a positive environmental impact. They are on the rise due to the surge of global environmentalism, especially after the creation of the United Nation’s Sustainable Development Goals (SDGs) in 2015. In Indonesia, green stocks can be found within the SRI-KEHATI index. Even though it is clear that the index has shown better performance than other major indices in Indonesia (i.e., IHSG, LQ45, and JII), it is still not yet entirely known how the SRI-KEHATI index holds up to an unprecedented crisis such as the COVID-19 pandemic. Using publicly available data of a total of 41 SRI-KEHATI constituents from 2015 to 2021 in Indonesia, this research uses panel data regression to determine how the COVID-19 pandemic affects the prices of green stocks and what factors significantly affect these stocks. The author found a significant and negative relationship between the presence of COVID-19 (COVID19) [D] and Net Profit Margin (NPM) [X2] toward stock prices within the SRI-KEHATI index (PRICE) [Y]. In addition, there is a significant and positive relationship between Earnings Per Share (EPS) [X1] and stock prices within the SRI-KEHATI index (PRICE) [Y]. Meanwhile, the variables that do not significantly affect the stock prices within the SRI-KEHATI index (PRICE) [Y] are Return On Equity (ROE) [X3], Debt to Equity Ratio (DER) [X4], and Firm Size (SIZE) [X5].